Cyclic loading of human articular cartilage: The transition from compaction to fatigue. (January 2017) - Kaplan, Jonathan T.; Neu, Corey P.; Drissi, Hicham; Emery, Nancy C.; Pierce, David M.
Abstract: Osteoarthritis and articular cartilage injuries are common conditions in human joints and a frequent cause of pain and disability. Unfortunately, cartilage is avascular and has limited capabilities for self-repair. Despite the societal impact, there is little information on the dynamic process of cartilage degeneration. We performed a series of cyclic unconfined compression tests motivated by in vivo loading conditions and designed to generate mechanical fatigue. We examined the functional (both stress–stretch and creep) responses of the tissue after recovery from a specified number of loading cycles, as well as histology and second harmonic generation microscopy images. The effect of compaction was complimented by the effect of fatigue in our unconfined compression tests. A three-way, repeated-measures mixed model ANOVA showed significant differences between loading with a physiologically relevant low magnitude, and two more severe loading magnitudes, in terms of the resulting specimen stiffness, time to equilibrium and thickness. There was a statistically significant effect of loading frequency on a specimen's time to equilibrium and significant interaction of force and frequency on specimen thickness and time to equilibrium. Increasing the number of loading cycles significantly impacted a specimen's effective stiffness and resulting thickness. We attribute permanent loss of mechanical function under cyclic loading to rearrangement and disruption of the collagen network and resulting proteoglycan (PG) aggregation, as seen in histological and second harmonic generation images, as a result of induced mechanical fatigue. Abstract : Graphical abstract: Abstract : Highlights: Performed cyclic compression with periodic tests of cartilages' functional responses. Load frequency significantly affected cartilages' time to equilibrium. Force–frequency interaction had significant effect on time to equilibrium, thickness. Increased load cycles significantly affected cartilages' stiffness and thickness. Multi-modal images provided insight to microstructural alterations in P'G and collagen.